DEVELOPMENT OF WORK BREAKDOWN STRUCTURE USING BUILDING INFORMATION MODELING AT UNJ - Rezi Berliana Yasinta; Adhi Purnomo; Alwan Izzudin (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
Building maintenance must also be carried out on campus buildings, because every day they are used by the academic community in their activities in large numbers. For that we need buildings that are safe, comfortable, and decent. Building maintenance in Indonesia is regulated in the Regulation of the Minister of Public Works No.24/PRT/M/2008 concerning Building Maintenance. This arrangement was updated with the passing of Law number 11 of 2020 concerning Job Creation. Based on this, it is also necessary to know the best building maintenance methods that must be applied based on the right approach. This study aims to plan a maintenance method for the L5 building on the UNJ Campus based on the Work Breakdown Structure (WBS) using Building Information Modeling (BIM). Based on a series of studies on the UNJ Campus L5 building that is integrated with BIM, it will improve the process of maintaining and repairing buildings. The results of this early stage research are expected to provide an overview and recommendations on how to maintain the UNJ Campus building.